Literary Engagement with the (Traumatic) Past - Bubíková, Šárka (American & British Studies Annual, 2015)
Review of History, Memory, Trauma in Contemporary British and Irish Fiction by Beata Piątek (Krakow: Jagiellonian University Press, 2014)